Variation of microbiological and small molecule metabolite profiles of Nuodeng ham during ripening by high-throughput sequencing and GC-TOF-MS - Cong Li; Yingling Zou; Guozhou Liao; Zijiang Yang; Dahai Gu; Yuehong Pu; Changrong Ge; Guiying Wang (Food Science and Human Wellness)
The internal microbial diversity and small molecular metabolites of Nuodeng ham in different processing years (the first, second and third year sample) were analyzed by high-throughput sequencing technology and gas chromatography-time of flight mass spectrography (GC-TOF-MS) to study the effects of microorganisms and small molecular metabolites on the quality of ham in different processing years. The results showed that the dominant bacteria phyla of Nuodeng ham in different processing years were Proteobacteria and Firmicutes, the dominant fungi phyla were Ascomycota and Basidiomycota, while Staphylococcus and Aspergillus were the dominant bacteria and fungi of Nuodeng ham, respectively. Totally, 252 kinds of small molecular metabolites were identified from Nuodeng ham in different processing years, and 12 different metabolites were screened through multivariate statistical analysis. Further metabolic pathway analysis showed that 23 metabolic pathways were related to ham fermentation, of which 8 metabolic pathways had significant effects on ham fermentation (Impact > 0.01, P < 0.05). The content of L-proline, phenyllactic acid, L-lysine, carnosine, taurine, D-proline, betaine and creatine were significantly positively correlated with the relative abundance of Staphylococcus and Serratia, but negatively correlated with the relative abundance of Halomonas, Aspergillus and Yamadazyma.